Forecasting The Export Value of Iron and Steel during The Covid-19 Pandemic - Rakhmawan, Sapto (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2021)
The COVID-19 pandemic has indirectly impacted international trade activities. This also affected the decline in Indonesian exports during 2020. Amid declining Indonesian exports, iron and steel commodities showed positive growth. Iron and steel export has contributed significantly to Indonesia's non-oil and gas export. Hence, the export of iron and steel is essential for boosting the economic development. Forecasting iron and steel export, therefore, becomes a necessity to assist the government in making the right policies related to the economic development. In this study, the ARIMA model will be discussed in-depth and will be applied to forecast the export value of iron and steel. We use export value of iron and steel data from January 2009 to December 2020. The results show that the ARIMA model is suitable for modeling iron and steel export data and the export value of iron and steel will increase for the next 12 periods.